PENERAPAN KAIZEN UNTUK MENGURANGI LOSS TIME DALAM PENINGKATAN PRODUKTIVITAS MESIN INFRARED WELDING (STUDI KASUS PT. MITSUBA INDONESIA) - Hartono, Hartono; Fatkhurozi, Fatkhurozi (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2021)
PT Mitsuba Indonesia is a factory engaged in the manufacture of electrical automotive spare parts. The LED winker lamp is the newest product whose production demand is always increasing. The large demand for LED winker lamp products must of course be balanced with the readiness of production machines which are always in good condition. But in practice, the results of the production achievement are still low, this is due to the high machine loss time, especially in infrared welding machines. This study discusses the application of kaizen which aims to find the causes of loss time, make improvements in order to reduce loss time and determine loss time and productivity after repairs are made. The method used to analyze the causes of loss time is to calculate the value of six big losses and analysis of the cause and effect diagram. The analysis results showed that the idling minor factor and stoppages losses caused by part drop error and the set up and adjustment losses factor caused by a change in the type of production jig. Improvements made to the part drop error were adding 1 set of regulators. Meanwhile, the change in the production jig type is to modify the locking system on the lower and upper heater jig. Based on these improvements, it was able to reduce the loss time to 4.86% and productivity to increase 7.50% in July. Loss time fell 4.70% and productivity increased 7.90% in August.Keywords: LED winker lamp, infrared welding machine, loss time, six big losses, productivity.